PENGARUH MOTIVASI, KARAKTERISTIK INDIVIDU,DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI PADA BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN PAMEKASAN - Nafisah Nafisah; Chamariyah Chamariyah; C. Sri Hartati (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to determine the motivation, individual characteristics and work experiencesimultaneously and or partially have an effect on the performance of employees in the General Sectionof Regional Secretary of Pamekasan Regency, Madura. Furthermore, this research is to know amongmotivation, individual characteristic and work experience which have dominant influence to employeeperformance at General Section of Regional Secretariat of Regency of Pamekasan. The type of researchused in this study is the type of explanatory research. This research was conducted in General Sectionof Regional Secretariat of Regency of Pamekasan with total sample of 64 employees. The results showedthat simultaneously, motivation, individual characteristics and work experience have a very significanteffect on employee performance and partially, motivation, individual characteristics and work experiencehave a significant effect on employee performance in General Section of Regional Secretariat ofPamekasan Regency. All independent variables partially have a significant effect on employeeperformance in the General Section of the Regional Secretariat of Pamekasan Regency; and motivationvariables have the most dominant influence in mempengruhi employee performance in the GeneralSection Regional Secretariat Pamekasan. Keywords: motivation, individual characteristics, work experience and employee performance